La réflexivité des professeurs des écoles stagiaires à l’aune de leur mémoire de master - Alain Garcia (Éducation et Socialisation)
The concept of reflexivity becomes important in the sphere of formation. We analyze Master’s degree written by student primary school teachers. There seem to be three forms in that reflexivity. We first discuss the terms associated with an scientist reflexivity, in 108 reports : this calculation produces a low result. In a sample of 18 textes, we observe then a usual reflexivity : that shows that school teachers would to limit themselves to the common interrogations. By downward logic, they order questioning, identification of preconceptions, clearmindedness, realization their mistakes and reaction accordingly from their pupils. This postponed reflexivity don’t restrain kind attitude of teachers. However, we notice that the school institution seems too high to advance easily.